1985
DOI: 10.1136/gut.26.8.802
|View full text |Cite
|
Sign up to set email alerts
|

Influence of morphine on the distal oesophagus and the lower oesophageal sphincter--a manometric study.

Abstract: USASUMMARY Basal pressure and relaxation of the lower oesophageal sphincter (LOS) as well as amplitude, duration and propagation velocity of peristaltic waves in the distal third of oesophagus were measured in 15 healthy adults (nine men and six women). A highly standardised technique was used employing manometric equipment including a low-compliance pneumohydraulic infusion system and a triple lumen recording catheter. After establishment of baseline manometry values the catheter was positioned with its dista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0
1

Year Published

1989
1989
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(38 citation statements)
references
References 7 publications
1
36
0
1
Order By: Relevance
“…Various studies with healthy volunteers have shown increased baseline LES pressure with incomplete relaxation when administering opioids. 6,7 Kraichely et al 8 confirmed these findings in clinical practice in a retrospective study of 15 patients with dysphagia and opioid consumption when manometry was performed. Our study evaluated the esophageal motility of patients with dysphagia and opioid consumption using HRM.…”
mentioning
confidence: 84%
“…Various studies with healthy volunteers have shown increased baseline LES pressure with incomplete relaxation when administering opioids. 6,7 Kraichely et al 8 confirmed these findings in clinical practice in a retrospective study of 15 patients with dysphagia and opioid consumption when manometry was performed. Our study evaluated the esophageal motility of patients with dysphagia and opioid consumption using HRM.…”
mentioning
confidence: 84%
“…It is not known if opium causes cancer directly through mutagenic compounds that are generated during pyrolysis of opium, or indirectly through the effect of its alkaloids (e.g. morphine) on the peristalsis of the intestinal tract (21, 22). We recently observed a higher risk of pancreatic cancer for opium ever users in a case-control study (23).…”
Section: Introductionmentioning
confidence: 99%
“…There was no statistical difference shown in LES pressure of subjects before and after propofol administration [3]. Other studies looking at the effect of conscious sedation on LES pressures have yielded mixed results [4–7]. In one study conducted on 19 infants and children, the effect of midazolam on LES pressure and motility was evaluated.…”
Section: Introductionmentioning
confidence: 99%